The influence of Celebrity Endorsement, Electronic Word of Mouth (E-WOM), and Live Streaming on Purchassing Decisions of Evangeline Perfume Products at FEB Udinus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Perfume is often used to enhance self-confidence and build a positive self-image, particularly among young people in social and academic settings. Thus, purchasing decisions are shaped not only by functional needs but also by emotional and social factors. This study examines how live streaming, electronic word-of-mouth (E-WOM), and celebrity endorsements influence consumers’ decisions to buy Evangeline perfume. A quantitative survey method was employed using purposive sampling, with respondents limited to FEB Udinus students who have experience with and knowledge of Evangeline products. This group was selected as they represent an active consumer segment for lifestyle and cosmetic goods. Data from 140 respondents were analyzed using multiple linear regression along with the classical assumption test. The results show that all three marketing variables significantly and positively affect purchase decisions, with live streaming being the most influential factor. These findings highlight the importance of interactive engagement, peer validation, and positive selection cues in shaping consumer trust and perception. Academically, this study contributes to consumer behavior and digital marketing research. Practically, the results suggest that perfume companies should prioritize live streaming campaigns, strengthen E-WOM strategies, and leverage celebrity endorsements to improve marketing effectiveness and increase sales.